2018
DOI: 10.1088/1555-6611/aaf22b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of He–Ne laser and argon laser irradiation on growth, germination, and physico-biochemical characteristics of wheat seeds (Triticumaestivum L.)

Abstract: Wheat seeds (Triticumaestivum L.) were exposed to two different types of lasers, a He-Ne laser (633 nm) and an argon laser (514.5 nm), to study their effects on growth, germination, and physiological and biochemical characteristics such as the amounts of chlorophyll a, chlorophyll b, and carotenoids. A significant increase in the growth characteristics was monitored and studied keeping in view the length as well as fresh and dry weight of shoots and roots. Similarly, plant pigment contents such as chlorophyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Figures 2A to 2C and 3A to 3D show that the growth of seedlings from laser-irradiated seeds at 530 nm was statistically different from that of the untreated plants. As reported by AlSalhi et al (2018) , laser treatment improves plant length and the dry weight of wheat seedlings. The outcome of the present study agreed with the earlier report by Podlesna et al (2015) on the impact of laser irradiation on the growth and flowering of the faba bean and white lupine.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Figures 2A to 2C and 3A to 3D show that the growth of seedlings from laser-irradiated seeds at 530 nm was statistically different from that of the untreated plants. As reported by AlSalhi et al (2018) , laser treatment improves plant length and the dry weight of wheat seedlings. The outcome of the present study agreed with the earlier report by Podlesna et al (2015) on the impact of laser irradiation on the growth and flowering of the faba bean and white lupine.…”
Section: Discussionmentioning
confidence: 53%
“…Studies by Ambika (2007) and Asghar et al (2016) on pre-sowing laser treatment also reported similar effects of a 20–35% increase in the rate of seed germination, possibly due to changes in the physiological state of the seeds and plants on exposure to different intensities of laser light. These changes in plant physiology can either stimulate or inhibit their development, depending on the power of the laser light ( AlSalhi et al, 2018 ). Other factors that could contribute to the improvement in seed germination is the energy transfer processes involved seed development ( Qiu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are several internal and external factors affecting the regulation of the physiological, biochemical, and growth parameters of plant seeds. Several studies revealed that the effect of laser treatment on plant characteristics could be related to the effect of light, electromagnetism, and temperature (Ri et al 2019;AlSalhi et al 2018). The seeds treated with laser revealed a higher germination percentage compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Wheat ( Triticum aestivum L.) is the most widely cultivated food crop throughout the world, with a large and complex hexaploidy genome (∼16 Gb) ( Appels et al, 2018 ). In the past decades, several mutagens have been used in wheat radiation research and breeding, such as ethyl methanesulfonate ( Chen Z. et al, 2020 ), gamma rays ( Bhat et al, 2020 ), laser ( AlSalhi et al, 2018 ), electron beam ( Wang et al, 2019 ), spaceflight ( Xiong et al, 2017 ), and 7 Li-ion beam ( Xiong et al, 2019 ). However, most of these studies focused on effects of radiation on physiology, biochemistry, morphology, and stress resistances.…”
Section: Introductionmentioning
confidence: 99%